The community of Camiling, Tarlac its history, people, institutions, and resources - Dy Tiapco, Melba C. 1917- (University of the Philippines], 1953)
This study presents a sociological study of Camiling, Tarlac. It described and analyzed the four aspects of the community: its history, people, institutions, and resources.